Simultaneous Interpretation with "Training Wheels" - Déjean Le Féal, Karla (Meta, 1997)
AbstractThis article deals with the teaching of simultaneous interpretation. It briefly reviews the procedures most commonly employed at the start of training in simultaneous and goes on to describe one particular approach: the use of consecutive interpretation to facilitate training in simultaneous. The rationale for and objectives of this approach as well as its practical application, advantages and results are discussed.